Feasibility of active handheld NDVI sensors for monitoring of lichen ground cover - Erlandsson, Rasmus; Arneberg, Marit Klemetsen; Tømmervik, Hans; Finne, Eirik Aasmo; Nilsen, Lennart; Bjerke, Jarle W. (Fungal Ecology, 2023)
Vegetation indices are corner stones in vegetation monitoring. However, previous field studies on lichens and NDVI have been based on passive sensors. Active handheld sensors, with their own light sources, enables high- precision monitoring under variable ambient conditions. We investigated the use of handheld sensor NDVI for monitoring pale lichen cover across three study sites from boreal heathlands to High Arctic tundra (62–79 ◦N), and compared it with Sentinel-2 satellite NDVI. NDVI decreased with increasing cover of pale lichens but the correlation between active and satellite NDVI varied between areas. NDVI values declined with lichen cover and ranged from 0.4–0.18 when lichen cover was above 40%. Active ground measurements of NDVI explained 81% of the variation in the satellite NDVI values in Svalbard (High Arctic), while the relationships were lower (~30% explained variation) in boreal regions (Troms-Finnmark and Røros). We show that active sensors are feasible for extracting information from lichen-dominated vegetation. Lichen Pale lichens Cladonia NDVI Active sensor Remote sensing Monitoring